The Death and Return of the Author: Criticism and Subjectivity in Barthes, Foucault and Derrida - Burke, Seán (Edinburgh Edinburgh University Press, 2008)
For the late twentieth century, the death of the author assumed a significance analogous to the death of God one hundred years previously. In this now classic study, Sean Burke both provides the first detailed explanation of anti-authorialism and shows how, even taken on its own terms, the attempt to abolish the author is philosophically untenable. Rather than developing a traditionally humanist defence, Burke effectively out-theorises theory through rigorous readings which demonstrate that the concept of the author remained profoundly active even and especially as its disappearance was being articulated.The question of the author, he argues, is not a question within theory but the question of theory. Building on a substantially revised second edition, Burke further explores the challenges faced by an authorial theory that is 'still to come'. Prompted by the responses to the passing of Jacques Derrida in 2004, he revisits the enigmatic borderlines between life and work, life and (authorial) death. Features of the third edition: a 5,000-word Preface which considers Derrida's legacy and the future of authorial theory; two new chapters which submit the biographical and autobiographical to independent theoretical scrutiny; and, a fully updated bibliography.
Keywords: Barthes, Roland -- 1915-1980; Foucault, Michel -- 1926-1984; Derrida, Jacques -- 1930-2004; 20th Century (1901-2000); Philosophy; Deconstruction